(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This paper argues that the nature and structure of world order characterised by American hegemony after the Cold war is changing. In cold war period, international system was bipolar and the power structure was primarily defined by militarily capabilities. But after disintegration of USSR in 1991, America emerged as the sole super power and the power dynamic in international system was a reflection of American interests. The hegemony of USA continued for a long time, but during this time period, other powers were getting stronger in various aspects like economy, polity etc. The emergence of these powers was a challenge to U.S hegemony.This changing world order led to the “rise of rest” which posed resistance to an America centric world order. The international structure that was incorporated with American ideals and values is being redefined and reshaped by interests, ideas and values of rising powers. This has led to a significant change in world order, where the unquestioned primacy of America is not only being challenged but also alternative perspectives and views are being asserted. The emerging powers have resulted in making the international structure more diffused. The world is now characterised by global interdependence and requires cooperation of all these major powers.In contemporary world, emergence of major powers like China and India is making a “multiplex world order” which entails “waning of the American- led liberal hegemonic order”. The present world order is characterised by growing role of non-American institutions, regional powers and regional organisations. Through institutions and organisations, rising powers are diffusing their values and norms and asserting their ideas and interests for playing greater role in international politics.The paper concludes by arguing that only a reciprocal accommodation of these powers’ interests by the United States can assure a stable and peaceful world order. The ongoing conflicts in the international system can only be resolved through cooperation and mutual accommodation.